PEMBELAJARAN MENULIS DENGAN METODE KOLABORATIF PADA SISWA SMP - Aminuddin, Aminuddin; Akbar, M Aris; Anwar, Khairil (Universitas Muhammadiyah Mataram, 2025)
This study aims to explore the application of collaborative methods in learning writing at the junior high school level through a Systematic Literature Review approach. The literature sources used are from trusted indexers such as SCOPUS, DOAJ, and Google Scholar. The results of the analysis show that collaborative methods have a significant positive effect on improving students' writing skills. Activities such as group discussions, cooperation, and mutual feedback are proven to increase students' active involvement, stimulate creativity, and develop critical thinking skills and the ability to organize arguments in a structured and logical manner. Supporting factors, such as the creation of an inclusive classroom environment, the teacher's role as an effective facilitator, and students' intrinsic motivation, play an important role in the successful implementation of this method. However, despite the positive impact of existing research, there are some gaps that need attention, such as the lack of research that deeply discusses the practical challenges faced by teachers and students in time management and the division of roles in groups.